Popularity of Korean Pop Music among Young Adults in Bangladesh - Sultana, Nigar; Nibir, Md. Mahdi-Al-Muhtasim (Journal of Journalism and Media, 2024)
K-pop, a South Korean popular culture, has gained global popularity due to its catchy music, choreography, and visuals. In Bangladesh, the youth are increasingly interested in K-pop, engaging on social media, and organizing events to celebrate the culture. This study investigates the factors contributing to K-pop’s popularity in Bangladesh, its impact on cultural practices and consumption behaviors, and the effects of online and offline platforms on fan behavior and merchandise purchases. Findings from the authors’ interviews with young adults suggest that K-pop’s popularity in Bangladesh is attributed to its exceptional production, relatable lyrics, intricate choreography, and multifaceted personalities of K-pop stars. Young fans’ identification with idols, performances, vocals, fashion, and outward appearances has also contributed to this genre’s enduring popularity. K-pop also shapes a cross-cultural sense of self among fans through online fan networks. This research sheds light on the factors that contribute to K-pop’s popularity among Bangladesh’s youth and explores the unique characteristics of K-pop, the significance of online fan networks, and South Korea’s cultural strategy. This research suggests that these insights can be used to enhance cultural dissemination efforts and support the expansion of the Bangladeshi entertainment industry.